Consistent Phosphenes Generated by Electrical Microstimulation of the Visual Thalamus. An Experimental Approach for Thalamic Visual Neuroprostheses - Panetsos, Fivos; Sanchez-Jimenez, Abel; Diaz-de Cerio, Elena R.; Diaz-Guemes, Idoia; Sanchez, Francisco M. (Frontiers in Neuroscience, 2011)
Most work on visual prostheses has centred on developing retinal or cortical devices. However, when retinal implants are not feasible, neuroprostheses could be implanted in the lateral geniculate nucleus of the thalamus (LGN), the intermediate relay station of visual information from the retina to the visual cortex (V1). The objective of the present study was to determine the types of artificial stimuli that when delivered to the visual thalamus can generate reliable responses of the cortical neurons similar to those obtained when the eye perceives a visual image. Visual stimuli Si were presented to one eye of an experimental animal and both, the thalamic RThi and cortical responses RV1i to such stimuli were recorded. Electrical patterns {RThi*} resembling RThi were then injected into the visual thalamus to obtain cortical responses {RV1i*} similar to RV1i. Visually- and electrically-generated V1 responses were compared. Results: During the course of this work we: (i) characterised the response of V1 neurons to visual stimuli according to response magnitude, duration, spiking rate and the distribution of interspike intervals; (ii) experimentally tested the dependence of V1 responses on stimulation parameters such as intensity, frequency, duration, etc. and determined the ranges of these parameters generating the desired cortical activity; (iii) identified similarities between responses of V1 useful to compare the naturally and artificially generated neuronal activity of V1; and (iv) by modifying the stimulation parameters, we generated artificial V1 responses similar to those elicited by visual stimuli. Generation of predictable and consistent phosphenes by means of artificial stimulation of the LGN is important for the feasibility of visual prostheses. Here we proved that electrical stimuli to the LGN can generate V1 neural responses that resemble those elicited by natural visual stimuli.